Right atrial strain and cardiovascular outcome in arrhythmogenic right ventricular cardiomyopathy. (2nd May 2022) - Anwer, Shehab; Guastafierro, Francesca; Erhart, Ladina; Costa, Sarah; Akdis, Deniz; Schuermann, Manuel; Hosseini, Sara; Winkler, Neria E; Kuzo, Nazar; Gasperetti, Alessio; Brunckhorst, Corinna; Duru, Firat; et al.
Abstract: Aims: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is characterized by progressive fibro-fatty infiltration of the myocardium and associated with adverse cardiovascular (CV) events. This study aims to examine right atrial (RA) deformation in ARVC and understand its association with CV outcomes. Methods and results: RA strain was determined in 50 patients with definite ARVC, compared with a matched control group of 50 healthy individuals, and analysed for outcome association over a median follow-up duration of 5 years. A subgroup of 30 ARVC patients with normal RA volume (ARVC-N group) was compared with 30 matched controls (Control-N), and the outcome was analysed separately. RA reservoir, conduit, and pump strain were significantly impaired in ARVC vs. control. Similar observations were made in the N-ARVC subgroup. Reservoir strain was associated with an increased risk of atrial arrhythmia (AA) [hazard ratio (HR) 0.88, P  < 0.01] and CV events (HR 0.92, P  < 0.01). Conduit strain also predicted AA (HR 1.02, P  < 0.01), while pump strain predicted CV events (HR 1.09, P  = 0.02). Reservoir strain improved the fitness of bivariable models for the association of RV end-diastolic area index, RV fractional area change, and RV global longitudinal strain with CV events. Conclusion: ARVC patients display impaired RA strain even when RA volume is normal. Reservoir and pump strain are associated with an increased risk of CV events. Reservoir strain improved model fitness for the association of RVGLS and other echocardiographic parameters with CV events. Graphical Abstract: Graphical Abstract Consort diagram on study design.